Линейные матричные неравенства и устойчивость движения импульсных систем - Слынько, В.И. (Видавничий дім "Академперіодика" НАН України, 2008)
The article presents some results allowing one to reduce the problem of stability of a linear system of differential equations with pulse action to that of compatibility of a system of linear matrix inequalities.